Proposed interior design of it Roo cafe at No.25, Ground Floor, Persiaran Ledang Height, Nusajaya, 79250 Johor Bahru, Johor Darul Takzim for it Roo Cafe Sdn. Bhd / Muhammad Afif Johari - Johari, Muhammad Afif (2012)
The final project for the student Diploma in Interior Design is a education towards the student's knowledge about the whole aspect on interior design that had been learnt from basic to the final presentation on the upgrading design. This courses will make student to practice what they learn during practical. Work student also should fulfill all the requirement needed and must follow the stage. Cafe is a informal restaurant, it may similarities with restaurant however it have in terms of difference in menu where menu is light meals. Usually cafe concept is casual or relaxed. The aim of this project is to understand the cafe design and it's flow traffic and also wants to bring a new concept & design idea to attract people come and try the menu serve by the cafe.The project is Proposed New Interior Design for It Roo Cafe at No.25, Ground Floor, Persiaran Ledang Height, Nusajaya, 79250 Johor Bahru, Johor Darul Takzim.The interview done is me with the owner of It Roo Cafe at 9.45pm. Several question had been asked regarding the management, about all the menu in his cafe, the arrangement of kitchen which includes the organization chart and the amount of staffs working there. I also asked about the operating hours which is everyday from 1.00pm to 10.00pm. Based on the observation done, the amount of visitors everyday is too many expecially at the peak hour such as lunch hour. The environment in the cafe its still good but the design is too gloomy and not enough space to support too many customer in one time. Nusajaya will become a main attraction to visitors whether locals or foreigners as Legoland Themepark its starting to launch the operation so this place is a very suitable to opened the business. The site take 5 minutes from Legoland Themepark. The existing client site use the colonial concept for their cafe, so the new design have to follow the concept but it will be apply in modern design style.The design of the existing premise is the place is too small compared with customer come to cafe in one period. The solution of this problem is opened new branch which is site is more big space and have a lot of parking space.